Lead-Induced Peripheral Neuropathy in a CKD Patient on Maintenance Hemodialysis - Rashid, Muhammad Humayoun; Bukhari, Syeda Neelam Yamin; Pervaiz, Henna; Sharif, Sheheryar; Chaudhery, Ghoza; Ali, Ayesha (Archives of Clinical and Medical Case Reports, 2021)
Peripheral neuropathy due to lead intoxication is a common presentation but secondary to maintenance hemodialysis is a rare find, especially with the international guidelines in place about the dialysate fluid required for hemodialysis. We report herein a 26-year-old Asian man who developed end-stage renal failure, followed by bilateral foot drop, in whom the maximal total blood lead was 34 µg/dL. Measurements of lead in his tibia and calcaneus by K-x-ray fluorescence, however, showed markedly elevated values. The foot drop cleared after few months of treatment with oral succimer and subsequent lead levels were below 10 µg/dL. The Lead source was investigated and found to be high in the dialysate used for maintenance hemodialysis. Succimer therapy along with dialysate meeting the international standards were used which resulted in improvement of the symptoms.